Irrigation depth on wheat by using line source sprinkler system - Faria, Rogério Teixeira de; Olitta, Antonio F. Lordelo (Pesquisa Agropecuaria Brasileira, 2014)
The purpose of this research was to examine the effects of the irrigation depth on yield and agronomic characteristics on wheat. The field experiment was carried out at the Experimental Station of ESALQ/USP (Piracicaba, SP) from May to August, 1980. The treatments, with six replications, consisted of six irrigation depths: 170 mm, 110 mm, 77 mm, 56 mm and 27 mm and no irrigation as control. Sixty-six mm of natural rainfall were observed during the growing season. Also 30 mm of water were uniformly added to experimental area at the early growth stages. Therefore, each treatment received a total of 266 mm, 206 mm, 173 mm, 157 mm, 123 mm and 96 mm of water depth. Water application was done by using the line source sprinpler system. Highest yields (2,839 to 3,019 kg/ha) were obtained with irrigation depths ranging from 150 mm to 200 mm, representing an increase of 66% over the control. Weight Thousand Kernel was adversely affected by the irrigation depth. Also, the increase of irrigation depth resulted in higher values for lodging, number of days from planting to maturity and plant weight.